Phytochemical Analysis and Comprehensive Evaluation of Pharmacological Activities, Isolation and Characterization of Bioactive Compound from the Bark of Sterculia urens Roxb. - Darapureddy, Chaitanya; Prasad, K.R.S.; R.S. Ch, Phani (Asian Journal of Chemistry, 2021)
The objective of the present study is to investigate the phytochemical constituents by qualitative and quantitative analysis, pharmacological activities such as antioxidant, antidiabetic, anti-inflammatory, thrombolytic and antibacterial activities of different crude extracts from bark of Sterculia urens Roxb. Further, the preparative HPLC isolation and spectroscopic characterization of the bioactive phytochemical constituents were also carried out. Different solvents such as n-hexane, ethyl acetate, methanol and water were used to prepare the crude extracts from the bark using Soxhlet extraction apparatus. DPPH free radical scavenging assay (antioxidant), α-amylase inhibition assay (antidiabetic), albumin denaturation assay (anti-inflammatory), blood clot lysis method (thrombolytic) and well-diffusion method (antibacterial) were performed for the determination of pharmacological activities of the bark extracts. The preparative HPLC analysis was carried for the separation and purification of bioactive compounds and the identification of isolated compounds was carried using 1H NMR, 13C NMR and mass spectroscopy. The quantitative estimation studies confirmed that methanolic extract contains 7.75 ± 0.141 GAE/g of phenolic compounds, 10.47 ± 0.033 mg of QE/g of flavonoids and 8.70 ± 0.047 mg/g of terpenoids. The ethyl acetate extract contains 2.16 ± 0.126 GAE/g of phenolic compounds whereas the aqueous extract contains 16.53 ± 0.055 mg/g of saponins. High DPPH radical scavenging was observed for methanolic extract with IC50 concentration of 85.38 ± 0.213 μg/mL. The α-amylase inhibition activity with IC50 concentrations of 145.67 ± 1.87, 98.36 ± 0.47 and 194.47 ± 0.55 μg/mL for ethyl acetate, methanol and aqueous extracts respectively. The albumin denaturation inhibition activity was found to be very high for methanolic extract with IC50 values of 132.08 ± 0.13 μg/mL which is near to the standard (107.13 ± 0.13 μg/mL). The % clot lysis of the methanolic extract in thrombolytic activity was found to be similar to the 100 μL of streptokinase (62.36 ± 0.140 %). Two terpenoids (One known terpenoid mansonone G and one new terpenoid) were isolated from the methanolic extract using preparative HPLC separation. Three known flavonoids (farrerol, apigenin and 6-hydroxyluteolin) and one new flavonoid were also isolated from the methanolic extract. The results suggested that bark extracts of Sterculia urens Roxb. having rich phytochemical constituents with high pharmacological activities.